200 Meters Freestyle Responses and Strategy Differences During Different Competition Rounds in Youth Competitive Swimmers - Tijani, Jed mohamed; Aloui, Ali; Said Hammed, Ahmed; Salhi, Amal; Ben Abderrahman, Abderraouf (Health Nexus, 2025)
The aims of the study were to analyze the physiological and perceptual responses, performances and strategy differences between competition rounds in youth competitive swimmers by examining possible differences between heats and semi-finals within the same competition day during the 200 meters freestyle event. Twenty-Two male swimmers volunteered to participate in this study. Only thirteen out of the sixteen qualified semi-finalists (age 16.8±0.6 years; weight 69.8±2.2 kg; height 178.3±3.9 cm) were taken into account for data analysis. Significant differences within and between groups were found for T200, HR, RPE and BLa (p < 0.001). From heats to semi-finals, Top 8 swimmers improved their performance by 5.72% with an increased value of HR (10.20%), RPE (35.56%) and BLa (67.30%), However, the remaining semi-finalists only saw a 2.92% improvement in timing and with an increased value of HR (5.17%), RPE (16.13%) and BLa (20.25%). These findings demonstrated that while the Top 8 swimmers swam more slowly in the heats, they exerted more effort in the semi-finals. This might be a tactic to conserve energy in order to provide their best effort in the semi-finals and rank in top to advance to the finals.